Strategi Menciptakan Keunggulan Bersaing Pada Perusahaan Industri Karet, Barang dari Karet dan Plastik di DKI Jakarta - Rina ardia Kusumawati; Waseso Segoro (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2020)
Based on BPS historical data during 10 years has been a decline PDRB value and number of Rubber, Rubber and Plastic Goods Industry companies in DKI Jakarta. This has an impact on the decrease of sales value, profit value, and market share of Rubber, Rubber and Plastic Goods Industry in DKI Jakarta. So, company should do a change in the company's strategy. Therefore, this research is conducted to analyze innovation, creativity, and market orientation affect to competitive advantage that can also affect to marketing performance. The research process uses census where 134 companies of Rubber, Rubber and Plastic Goods Industry that listed in BPS of DKI Jakarta Province in 2016 to be research object. Collecting data uses questionnaire with Likert scale which from 1 (strongly disagree) to 7 (strongly agree). The data analysis uses Structural Equation Modeling (SEM) with AMOS 22 program. The research proves that innovation, creativity, and market orientation have positive and significant affect to competitive advantage. Furthermore innovation, creativity, market orientation, and competitive advantage have positive and significant affect to marketing performance. Therefore, companies need to pay attention to innovation, creativity, and market orientation so that they have high competitiveness that can improve the company's marketing performance.